The Evidence Base for Prophylactic Antibiotics in Patients Receiving Extracorporeal Membrane Oxygenation. Issue 1 (January 2016) - O'Horo, John C.; Cawcutt, Kelly A.; De Moraes, Alice Gallo; Sampathkumar, Priya; Schears, Gregory J.
Abstract : The aim of this review was to evaluate evidence for the use of antibiotic prophylaxis in patients receiving extracorporeal membrane oxygenation (ECMO) therapy. We systematically reviewed MEDLINE, EMBASE, Scopus, and other major databases and included any study that reported rates of infection and whether antibiotic prophylaxis was a part of therapy for patients receiving ECMO. We abstracted rates of infection, microbiology of isolates, prophylactic practices, and individual study inclusion and exclusion criteria. Among 11 studies identified, rates of infection were fairly uniform regardless of prophylaxis use, and the only two studies that directly compared outcomes with and without prophylaxis found no benefit. The causative infectious organisms were heterogeneous, which gives no clear rationale for any particular prophylactic strategy. Although infections during ECMO are serious complications that must be prevented, there is no good evidence to support routine use of prophylactic antibiotics in most patients. Certain subpopulations, such as those with open chests, may have an indication for prophylaxis, but evidence is poor. Future studies should investigate the role of other approaches to infection prevention, such as chlorhexidine bathing and preferential elective cannulation. Abstract : Supplemental Digital Content is available in the text.